2005
DOI: 10.1152/jn.01159.2004
|View full text |Cite
|
Sign up to set email alerts
|

On the Division of Cortical Cells Into Simple and Complex Types: A Comparative Viewpoint

Abstract: Ibbotson, M. R., N.S.C. Price, and N. A. Crowder. On the division of cortical cells into simple and complex types: a comparative viewpoint. J Neurophysiol 93: 3699 -3702, 2005. First published January 19, 2005 doi:10.1152/jn.01159.2004. Hubel and Weisel introduced the concept of cells in cat primary visual cortex being partitioned into two categories: simple and complex. Subsequent authors have developed a quantitative measure to distinguish the two cell types based on the ratio between modulated responses at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…While previous studies have clearly demonstrated that F1/F0 ratios are bimodally distributed in the anesthetized animal (De Valois et al, 1982; Dean & Tolhurst, 1983; Ibbotson et al, 2005; Mata & Ringach, 2005; Priebe et al, 2004; Ringach, Shapley et al, 2002; Schiller et al, 1976b; Skottun et al, 1991), the number of studies that used the F1/F0 ratio as a criteria to classify cortical cells is much larger than the number of studies that have demonstrated a significant bimodal distribution (see Table 1). There are multiple examples of studies that measured the distribution of F1/F0 ratios and failed to find significance for bimodality as, for example, Mata & Ringach (2005) in anesthetized primate and Heimel et al (2005) in anesthetized squirrel.…”
Section: Discussionmentioning
confidence: 92%
“…While previous studies have clearly demonstrated that F1/F0 ratios are bimodally distributed in the anesthetized animal (De Valois et al, 1982; Dean & Tolhurst, 1983; Ibbotson et al, 2005; Mata & Ringach, 2005; Priebe et al, 2004; Ringach, Shapley et al, 2002; Schiller et al, 1976b; Skottun et al, 1991), the number of studies that used the F1/F0 ratio as a criteria to classify cortical cells is much larger than the number of studies that have demonstrated a significant bimodal distribution (see Table 1). There are multiple examples of studies that measured the distribution of F1/F0 ratios and failed to find significance for bimodality as, for example, Mata & Ringach (2005) in anesthetized primate and Heimel et al (2005) in anesthetized squirrel.…”
Section: Discussionmentioning
confidence: 92%
“…Bardy et al (2006) have shown that the response properties of some classes of complex cells can be converted to putative simple cells depending on influences originating from the classical receptive field. The experimental results can, however, be strongly dependent on the experimental conditions (Kagan et al 2002; Mata and Ringach 2005; Chen et al 2002) and bimodal distributions have been found by Kagan et al (2002), Ibbitson et al (2005), and Chen et al (2002). Moreover, Martinez and Alonso (2003) argue that a large body of neurophysiological evidence indicates that simple cells are a separate population from the total of cortical cells in cat visual cortex.…”
Section: Relations To Previous Workmentioning
confidence: 98%
“…It has been reported in the past that the frequency distributions of F1/F0 spike-response ratios (to optimized grating patches) of neurons recorded from areas V1 of anesthetized domestic cats (Li et al 2003;Movshon et al 1978aMovshon et al , 1978bSkottun et al 1991), macaques (De Valois et al 1982;Ringach et al 2002;Skottun et al 1991), laboratory rats (Girman et al 1999), house mice (Niell and Stryker 2008), and tammar wallabies (Ibbotson et al 2005) are not unimodal, with frequency "dip" at the intermediate F1/F0 ratios of 0.7-1.3, that is, close to the ratio of 1. The apparent bimodality of frequency distribution of F1/F0 spike-response ratios has been invoked in support of the argument that in area V1, at least, cells with F1/F0 ratios Ͼ1 and these with ratios Ͻ1 represent two distinct groups of neurons.…”
Section: Frequency Distribution Of F1/f0 Spike-response Ratios Of Arementioning
confidence: 99%